The levels of some antioxidant vitamins, glutathione peroxidase and lipoperoxidase during the anaesthesia of dogs - Naziroglu, M; Günay, C (Wiley-Blackwell, 1999)
The aim of this investigation was to determine serum levels of vitamin A, E, beta carotene, glutathione peroxidase (GSHPx), lipid peroxidation (MDA) and biochemical and haematological parameters during enflurane anaesthetised dogs. Ten kangal dogs were used and all animals were anaesthetised with enflurane for two hours and blood samples were taken before and 30, 120 minutes, 24 hours and 7 days during the anaesthesia. Vitamin E and beta carotene content were significantly (p < 0.05 and p < 0.01) higher before anaesthesia than after whereas serum GSHPx activity was not statistically different. However, serum levels of vitamin A and MDA were significantly (p < 0.05) increased during the anaesthesia. In general, serum levels of aspartate aminotransferase, alanine aminotransferase, albumin, glucose, urea and creatinine were significantly (p < 0.05 and p, < 0.01) increased during anaesthesia and returned to near normal values after 7 days of anaesthesia, whereas the white blood cell count was significantly (p < 0.05 and p < 0.01) decreased during the anaesthesia. However, the red blood cell count, haemoglobin and packed cell volume values, and levels of total cholesterol, triglycerides, total protein and globulin were apparently not influenced by the anaesthesia. In conclusion, we observed that the serum level of vitamin E and beta carotene were significantly decreased, whereas serum MDA and vitamin A levels were significantly increased during the enflurane anaesthesia. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: anaesthesia; vitamin E; metabolism; lipoperoxide; enflurane; dog